PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN EKOWISATA TAMAN HUTAN RAYA GUNUNG TUMPA H.V. WORANG PROVINSI SULAWESI UTARA - TUNAS, MAYA; LIANDO, DAUD; PRATIKNJO, HENY MARIA (Sam Ratulangi University, 2019)
This study aims to determine and analyze community participation in: decision making(participation in decision making), participation in implementation (participation in implementation),participation in utilization of results (participation in benefit), and participation in evaluation (participationin evaluation).This type of research used in this study is a qualitative descriptive study with representativeelements of: Head of HANURA UPTD, Head of Protection Section for Natural Resources Conservationand Community Empowerment. Camat, Lurah, Tua Hukum, and the Community. Data collectiontechniques using observation, interviews and documentation. Data analysis techniques are carried outthrough the stages of organizing data, data reduction, data grouping, data analysis and drawingconclusions. Data triangulation is carried out to check the validity of data and information, then the resultsof data analysis are presented using words written words.The results show that participation in decision making has not been demonstrated by the community due tothe lack of opportunities in the preparation of program plans and activities, so that it cannot convey whatthey need, where the community needs community empowerment activities. Participation in theImplementation was shown by the community through the presence in Focus Group Discussion (FGD) andsocialization, while the opportunity to utilize the available facilities was not yet available because it waswaiting for cooperation with the private sector. Participation in Utilization Results are only limited toutilizing existing natural resources and have not utilized existing tourism activities to empower thecommunity. Participation in the Evaluation does not yet exist because there is no opportunity for thecommunity to participate. It is recommended that the government involve the community to participatestarting from the public consultation, outreach. The community can manage the surrounding natural area eventhough the government has involved the private sector in developing TAHURA, also involving thecommunity in the Evaluation stage to provide input for further program improvementKeyword: Community Participation, Ecotourism